Development of Computer Programto determine Runway Length Requiredfor Airport Design - I. AL-Kubaisi, Mehdi (Iraqi Journal of Civil Engineering, 2008)
AbstractSelecting a design runway length is one of the most important decisions an airportdesigner makes. The length required to accommodate the most demanding airplanesanticipated to use an airport is a fundamental airfield design factor. This paperdescribes the important role which the runway length is playing in any proposedairport to be designed.Computer program named (RUNWLD) was developed during this researchperiod to determine the runway length depending on the Federal AviationAdministration (FAA) methodology. (RUNWLD) predicts the planned and basicrunway lengths for various mix of airplanes anticipated to use a proposed airports.The program was written in visual basic programming language. The dataused in this program is concluded from the charts, tables, and circular advisoryadopted by (FAA) methodology. The developed program (RUNWLD) is easy tooland user friend, in addition to that it save time while getting results comparing tothe traditional (FAA) method.Keywords: runway length, airport, airplane, FAA, program